Estado nutricional en pacientes pediátricos menores de 5 años con infecciones respiratorias agudas bajas atendidos en el Hospital Iquitos, 2023 - Moran Gonzalez, Eliangel de los Santos (2024)
Acute respiratory infections are a leading cause of morbidity and mortality worldwide. They can be divided into upper respiratory tract infections, which include nasopharyngitis, laryngitis, and sinusitis, and lower respiratory tract infections, which include bronchiolitis, bronchitis, and pneumonia. Pneumonia is by far the most common type of lower respiratory tract infection. There are 150 million new cases of pneumonia worldwide each year, more than 90% of which occur in developing countries.1 In Peru, a total of 433,854 cases of acute respiratory infection (not pneumonia) and 4,254 cases of pneumonia have been reported as of week 14 of 2023, with an incidence rate of 17 per 10,000 children under 5 years of age. Loreto had 38 episodes of pneumonia per 10,000 children under 5 years of age, followed by the departments of Madre de Dios, Ucayali, and Amazonas with 26 to 27 episodes of pneumonia per 10,000 children under 5 years of age.17 Nutritional status is directly related to disease responsiveness, and nutritional deficiencies increase the risk of infectious diseases such as acute respiratory infection (ARI). Although the global prevalence of stunting and underweight among children under five has declined since 1990, the overall improvement has been insufficient, and millions of children remain at risk. 10 This is a descriptive, retrospective, cross-sectional, analytical, retrospective study. The sample will be all patients older than 1 month and younger than 5 years who were hospitalized for Acute Respiratory Infections (Bronchiolitis, Pneumonia, Acute Bronchitis) in the Pediatrics Service of the Hospital Iquitos "Cesar Garayar Garcia", during the period January to May 2023.